(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This study aimed to investigate the role of retrieval and anticipation in building the characters of Abdulaziz Al-Farsi’s novel “The Erath cries and Saturn laughs” through examining the relationship of the techniques of retrieval and anticipation with the main and minor characters in the novel, highlighting the role of the novelist in presenting his characters through both aspects of time; the retrieved and anticipated, and revealing the role of these two time techniques in ordering the events of the novel in a timeline through which readers can imagine the characters of the novel and the sequence of their timeline in creating the events of the novel. The study sought to highlight the role of time in drawing the features of the novel’s characters and to identify their dimensions through the techniques of retrieval and anticipation. In addition, the study tried to identify the types of the characters in terms of the aspects of their roles, their development and their consistency and the way in which time represented a tool to measure the development of the characters through highlighting the role of the two time periods, the retrieved and anticipated, in revealing the states of instability in the external and internal dimensions of some characters in the novel. This was also done through identifying the situations in which the retrieved and anticipated time periods of the novel played a major role in motivating the characters to express their inner feelings, illustrating the mechanisms of employing these retrievals and anticipations and showing how the novelist succeeded in utilized such retrievals and anticipations as elements of suspense through which he highlighted the relationships of the characters with one another. The study followed the descriptive analytical approach to provide answers to its questions and achieve its objectives.